Análisis de contenidos de la programación desde el enfoque de la actual Ley Orgánica de Comunicación en TV Color y Elite TV - Borja Rivera, Madisson Fernando (2016)
This project aims to investigate media audiovisual TV Color and Elite TV media city of Latacunga, later to make a diagnosis of managing programming focusing on its timeslot and quality of content. The lack of programs that show quality content that is scarce in the canals of the city and several of them have large breaches in the current Communication Law why carried out this research project. The research method that was used for it is the direct observation relying on a data sheet created specifically to control the type of content and times that are transmitted, watching each of the programs broadcast throughout the day in the media audio visual above. For the media to make further good content restructuring and improve the quality of them and even generate new television programs, but this requires that the media have a clearer view of the current media law.